Beurteilung von Ausbaumaßnahmen in Kläranlagen zur Verringerung der Ausbreitung von fakultativ pathogenen Antibiotika-resistenten Keimen in Oberflächengewässern - Heß, Stefanie (Karlsruher Berichte zur Ingenieurbiologie / Institut für Ingenieurbiologie und Biotechnologie des Abwassers, Karlsruher Institut für Technologie, 2015)
Antibiotic resistance is one of the most serious health threats of the 21th century. Whereas resistance levels are permanently surveyed in hospital, little is known about the fate and the behavior of antibiotic resistant bacteria living in aquatic environments. The present work addresses the resistance levels in fecal contaminated surface waters and evaluates advanced sewage treatment technologies concerning their elimination of facultative pathogenic and antibiotic resistant bacteria.